Athletic profiling of young swimmers: Physical tests and training practices - Mohammed Hamdi; Khalid El Mouahid; Samy Smouni; Mohammed Benhida; Omar Ajaja; Abdelkhaleq Legssyer (CV. FOUNDAE, 2026)
Background: Assessing athletic qualities, coach training, and sports infrastructure can influence athletic performance. This study examines the link between the swimmer’s athletic profile test and the role of athletic quality assessment in optimizing performance. Aims: To study the role of athletic quality assessment among Moroccan coaches and technical directors in the physical preparation of their swimmers, in relation to sports infrastructure. Method: twenty elite swimmers of both sexes, aged 14 to 16, and 33 coaches and technical directors participated in this study. An athletic profile assessment test was conducted, and a survey was conducted on the role of athletic quality assessment across various aspects, including training, athletic quality assessment, and constraints related to sports infrastructure. Chi-square and independence correlation tests were used to analyze the significance and correlation between variables. Results: The swimmers’ athletic profile tests were exploratory. No significant difference was found between participants’ training and their physical preparation practices for training (p = 0.085 > 0.05). No significant difference was found between participants’ status and the location of their physical preparation (p = 0.939). No significant correlation was found between the importance of the assessment and participants’ gender in the Mann-Whitney test (46 with exact; p = 0.540 > 0,05). Conclusion: Our results suggest that implementing athletic profile testing for swimmers can be useful for selecting and customizing training programs and improving performance in specific disciplines. Our findings indicate that the importance of physical preparation is not linked to coach training or to constraints on sports infrastructure.